Diseño y construcción de un equipo tamizador transportador para el procesamiento de material pétreo - Gualpa Toapanta, Jonathan Xavier (2019)
The present thesis has the purpose of optimizing the time in the sieved process through the implementation of a sifter conveyor equipment to process de oil material (granulation) for the bricklayers of the Guaytacama Parish, Cevallos neighborhood, by the machine, we reduce the time in the sieved process and the production was improved because the sieved material is used to flatten (smoothed) the walls, so on. The sifter conveyor equipment was built to be operated in an intuitive and ergonomic way, in addition to this it will solve the capacity of sieving in cubic meters and the time of the production process. It is important to mention that it was taken in account the different types of sieving in stock with their advantages and disadvantages of each one, from which it was selected through a matrix selection of rotational sifter equipment actuated by the system with movement transmission by a vibrating motor, it was also included a conveyor tape of 2,20 meters of large and 40 centimeters of width which helped to transport the material to a safe place where was compiled the sifted material. For which it was also installed a control cabinet for the turning on and off of the sifter conveyor equipment. Besides for the machine construction it was used the cutting, bending and welding as more important operations processes. In which the machine had a production of 553,35 kg/h doing the sieving process with the sifter conveyor equipment.